Implementation of sharia in the management of the Ibrahim Sharia Hotel and the Prayer Sharia Hotel in Semarang - Guritno, Bambang; Maria TH, Aletta Dewi; Pradapa, Sri Yulianto Fajar; Supriyanto, Sapto; Tirtana, H. Diovany (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
In halal tourism there is an element of hospitality. How can hospitality in Central Java grow according to sharia, of course in hotels there must be facilities for places of worship. By realizing this, tourists who are looking for halal tourism in Central Java can feel comfortable traveling. The purpose of research on the application of sharia, the differences and similarities in the application of sharia in management. As for the purpose of knowing sharia in management, the differences and similarities in its application. This research uses a qualitative approach. Researchers observed the research location as a whole according to the problem and also interviewed the hotel. The population in this study is the management, all employees and visitors. The method used in this study is an analysis based on general data and then specific conclusions are drawn (deductive method) and the method used to compare the data drawn into new conclusions (comparative method). If the population is <100 people it is better to take all of them, if the population is >100 people then the sample taken is between 10-15% or 20-25%. Therefore, the samples in this study were owners, employees and visitors between 10-15 people as informants. Based on the research results, it can be concluded that the hotel is a type of accommodation that uses part or all of the building area to provide lodging, eating, drinking, and other services for the public that are managed commercially.